Melkersson-Rosenthal Syndrome in a Patient with Systemic Lupus Erythematosus: A Rare Comorbidity - Yıldız DEĞİRMENCİ; Şenol KOBAK; Ceyda HAYRETDAĞ ÖRS; Handan ÖZIŞIK KARAMAN (Archives of Rheumatology, 2012)
Melkersson-Rosenthal syndrome (MRS) is a rare granulomatous disease characterized by recurrent orofacial edema, facial palsy, and a fissured tongue. In this article, we report a 23-year-old female case with recurrent peripheral facial palsy, mild orofacial edema, and a fissured tongue. She had spots in her feet with a history of oral aphthous ulcers and experienced a relapse once a year. The neuroimaging results were normal, however the laboratory examination indicated systemic lupus erythematosus (SLE). This rare case is presented to emphasize the complete triad of MRS concomitantly occurring with SLE in this patient.